Sistem Monitoring Inventory Souvenir berbasis AppSheet: Inovasi Manajemen Stok - Fauziyyah, Aghniya Tsaniya; Sutisna, Ma’mun (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
Technological advances encourage digitalization in various sectors, including inventory management. Information systems have an important role in collecting, storing, and presenting data into useful information. PT PLN (Persero) UP3 Bandung faces obstacles in managing souvenir inventory stocks, such as delays in data access, recording errors, and inefficient manual processes. This research aims to develop an AppSheet-based souvenir inventory monitoring system as an efficient and integrated digital solution. This type of research is software engineering research, with a Waterfall development model consisting of requirements analysis, system design, implementation, and testing. The testing we do uses black box testing which aims to evaluate the functionality of the application according to specifications. The data collection we used was interviews and observations. The result of our findings is a system that provides reporting features to facilitate monitoring of souvenir inventory stock based on AppSheet which is designed to replace the manual recording process. The test results prove that the system runs well as needed and gets a positive response from the owners and employees of PT PLN (Persero) UP3 Bandung. This system can improve efficiency, recording accuracy, reduce the risk of human error, and speed up the monitoring process. With this system, it has the potential to be replicated in other units as part of the digital transformation of the public sector.